Treating Excessively Slow Responding of a Young Man With Asperger Syndrome Using Differential Reinforcement of Short Response Latencies - Tiger, Jeffrey H (The Society for the Experimental Analysis of Behavior, 2007)
Fjellstedt and Sulzer-Azaroff (1973) used differential reinforcement of short latencies to decrease a child's latency to comply with instructions. We replicated this contingency with a young man diagnosed with Asperger syndrome across two tasks (question answering and math problem solving). We added a differential reinforcement contingency to teach the participant to discriminate between math problems that could be answered rapidly and those that required more time for accurate performance.